The Impact of Interest: Firms' Investment Sensitivity to Interest Rates - Lea Best; Benjamin Born; Manuel Menkhoff (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
The sensitivity of firms' investment to interest rates is central to the transmission of monetary policy, yet direct firm-level evidence is scarce. We provide such evidence using the ifo Business Survey of German firms, combining hypothetical vignettes, open-ended questions, and rich firm-level information. The vignette design implies a semi-elasticity of investment to loan rates of 7 percent—a partial-equilibrium effect roughly half the total corporate investment response to monetary policy shocks. Adjustment is heterogeneous: many firms do not adjust, often citing cash buffers or a lack of profitable opportunities, while adjusters revise plans sharply. Responsiveness is dampened by sticky hurdle rates but amplified by financial constraints, labor shortages, and capital durability. Managers' narratives about monetary policy transmission to investment emphasize the direct interest rate channel, rarely mentioning general-equilibrium channels, and many do not consider monetary policy changes. Local projections show the direct interest rate channel plays a first-order role in output dynamics after monetary policy shocks.
Keywords: D25; E43; E52; G31; 330; interest rates; firm investment; survey experiment; monetary policy; narratives; hurdle rates; aggregate investment